Diagnostic Value of Concentration of Circulating Cell-Free DNA in Breast Cancer: A Meta-Analysis - Yu, Dandan; Tong, Yan; Guo, Xinnian; Feng, Lingfang; Jiang, Zhaoqiang; Ying, Shibo; Jia, Junlin; Fang, Yuan; Yu, Min; Xia, Hailing; Shi, Li; Lou, Jianlin (Frontiers in Oncology, 2019)
The diagnostic value of the concentration of circulating cell-free DNA (cfDNA) for breast cancer has generated inconsistent results. The aim of this study was toevaluate the the diagnostic value of the concentration of cfDNA for breast cancer bymeta-analysis. Studies were retrieved by searching PubMed, Cochrane Library and Web of Science before June, 2018. Sensitivity, specificity, diagnostic odds ratio (DOR), the summary receiver operating characteristic (SROC) curve, and the area under curve (AUC) were used to summarize overall diagnostic performance. The random-effects model was used to calculate the pooled statistics. Subgroup analysis and meta-regression analysis were carried out to detect the source of heterogeneity.A total of 13 studies were identified with 1087 breast cancer patients and 720 healthy controls. Overall,the pooled sensitivity and specificity of concentration of cfDNA for breast cancer were 87% (95% CI, 73%-94%) and 87% (95% CI, 79%-93%), respectively. The pooled DOR was 32.93 (95% CI, 13.52-80.19) and the SROC curve revealed an AUC of 0.93 (95% CI,0.91-0.95). Meta-regression analysis showed that no covariate had a significant correlation with relative DOR (RDOR). Publication bias was not detected in this meta-analysis.This meta-analysis indicatesthat the concentration of cfDNA has potential diagnostic value for breast cancer and plasma may be a better source ofcfDNA in detection of breast cancer.